2015
DOI: 10.1161/atvbaha.115.305380
|View full text |Cite|
|
Sign up to set email alerts
|

Atherosclerosis

Abstract: Summary Mechanistic studies over the past decades using in vitro systems, animal models, and human tissues have highlighted the complexity of pathophysiological processes of atherosclerosis. Hypercholesterolemia, as one of the major risk factors for the development and progression of atherosclerosis, is still the focus of many mechanistic studies and the major therapeutic target of atherosclerosis. Although there is a dire need to validate many experimental findings in humans, there is a large number of approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 127 publications
0
96
0
4
Order By: Relevance
“…Although atherosclerosis specifically affects arterial vessels, as opposed to the venous system, and is marked by the subendothelial accumulation of lipids and lipid-laden foam cells (40), it shares the recruitment of circulating leukocytes and monocytes to the developing and progressing lesions with other inflammatory processes that involve the vasculature. Reelin has been reported to affect thrombosis and hemostasis (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Although atherosclerosis specifically affects arterial vessels, as opposed to the venous system, and is marked by the subendothelial accumulation of lipids and lipid-laden foam cells (40), it shares the recruitment of circulating leukocytes and monocytes to the developing and progressing lesions with other inflammatory processes that involve the vasculature. Reelin has been reported to affect thrombosis and hemostasis (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Some substantial changes contribute to the pathological changes of atherosclerosis, including dysfunction of vascular wall cells [i.e., endothelial cells (ECs) and vascular smooth muscle cells (VSMCs)] and the recruitment of leukocytes [24]. According to previous studies, dysfunctional ECs play a pivotal role in atherosclerosis by impairing endotheliumdependent vasodilatation, increasing vascular permeability, up-regulating the expression of chemokines/adhesion molecules and decreasing endothelial regeneration [24]. So, some biomarkers which impact on endothelial function might reflect the condition of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inhibition of inflammatory response and ROS production may be beneficial in preventing the development of AS . Endothelial cell dysfunction is another major cause AS development . Although primary HUVECs are considered to be the best model for endothelial function studies, they may undergo phenotypic change with passages and may require specialized culture media for growth.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is a critical factor in the pathogenesis of AS . An increasing number of studies have demonstrated the close association of vascular inflammatory response and oxidative stress with endothelial dysfunction .…”
Section: Introductionmentioning
confidence: 99%